A systematic review of the literature on the application of blockchain in the health supply chain - Araújo, Andre Ricardo Cavalcanti (2022)
Objective of the study: This article aims to present a systematic literature review on the application of blockchain in the healthcare supply chain.Relevance / originality: The relevance and originality consist in the presentation of a systematic literature review that focuses and considers the concepts of blockchain, healthcare and supply chain as equally important, in the studied time frame.Methodology / approach: The systematic literature review followed a protocol based on Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA), performing the search in eight databases, selecting conference and journal articles based on their content in sequential steps.Main results: As a result, 122 publications were selected. The number of publications in the field has been found to grow rapidly, and sensors and the Internet of Things (IoT) are two prominent minor topics. Three research challenges were raised.Theoretical / methodological contributions: Provide understanding to academics and professionals in the field about the state of the art of applying the blockchain in the healthcare supply chain, both in terms of the evolution of the literature, as well as in terms of raising new research.Social / management contributions: Raising discussions on solutions to healthcare supply chain issues, involving for example data integrity and privacy in electronic medical reports, drug counterfeiting and the use of sensors and the internet of things.